A systematic map of knowledge exchange across the science‐policy interface for forest science: How can we improve consistency and effectiveness?. Issue 1 (14th March 2023) - Westwood, Alana R.; Hutchen, Jenna; Kapoor, Tyreen; Klenk, Kimberly; Saturno, Jacquelyn; Antwi, Effah K.; Egunyu, Felicitas; Cortini, Francesco; Robertson, Manjulika; Le Noble, Sophie; Wang, Jonathan; Falconer, Matthew; et al.
Abstract: Knowledge produced by scientists is essential to the policy and practice of managing natural resources, including forests. However, there has never been systematic mapping of which techniques in knowledge exchange (KE) have been applied in the forest sciences, by whom, and to what effect. We examined KE techniques documented in the forest sciences globally. We used standardized search strings in English and French across two academic search engines (BASE and Scopus) and a specialist website (ResearchGate) to locate relevant items. We screened items, extracted data, conducted qualitative and quantitative analysis, and built a network visualization diagram to demonstrate knowledge flow. Our final map included 122 items published from 1998 to 2020, with most published after 2010. Items mentioned organizations from 66 countries as knowledge producers or users. The interactive network visualization diagram displays linkages between organizations, sectors and countries. We found that most of the KE activity involved the Global North (89%). Governments were the most common knowledge users, and industry was frequently reported as a user but rarely a producer. Academia was both producer and user. Indigenous, local, traditional or community knowledge was included in 24% of items, but these communities were not associated with any coauthor affiliations. Reported funders were universities, governments, non‐profits or foundations. We found 90 unique terms in the items related to KE with less than 25% of terms used in more than one item. Fifteen per cent of item keywords related to KE. The most commonly identified enabling conditions for KE were trust, funding and established relationships, while major barriers were challenges for translation of science and lack of time. To improve searchability of information related to KE and encourage a culture of considering KE in scientific research and forest management work, we recommend a common lexicon of 'knowledge exchange'/'échange de connaisances'. We recommend that more effort be given to forest science‐related KE connections between the Global North and South as well as a deliberate collection of evidence for the effectiveness of KE techniques. Researchers and practitioners can use our KE typology to identify their goals and design appropriate evaluation measures. Abstract : A new systematic map of literature about knowledge exchange in forest science finds a muddy landscape of competing terminology and lack evidence of the effectiveness of knowledge exchange techniques. We map the field and the types of knowledge exchange used as well as its enabling conditions and barriers. We suggest a common approach and terminology to unite the discipline to support more effective knowledge exchange efforts in future.